Microplaston artificial polymers in the Miass River and Lake Turgoyak (Southern Urals, Russia) in the early stages of colonisation - Ph. V. Sapozhnikov; O. Yu. Kalinina; S. V. Vostokov (Юг России: экология, развитие)
Aim. To identify the composition and features of the spatial structure of microfouling (microplaston) during the early stages of colonisation of the surfaces of artificial polymer films (LDPE) in the natural habitats of the Miass River and Lake Turgoyak (Southern Urals). The early stages of polymer microfouling which create the basis for further complexity of its spatial mosaic are considered, taking into account the surface microlandscape and the possibilities it creates for the location of community components.Materials and Methods. Fragments of polymer films (LDPE) manufactured for household use were collected in the waters of the Miass River and Lake Turgoyak in June 2023. Samples were selected that were exposed in natural reservoirs for at least several months. Analysis of the composition, structure and spatial organization of microplastonic communities was carried out using light and SEM microscopy.Results. The microplaston in the early stages of growth varied significantly among the habitats studied. On LDPE films from the Miass River they were dominated by sessile armored amoebae (Granofilosea: Microgromiidae), attached diatoms (Bacillariophyta: Achnanthaceae, Cocconeidaceae) developed as a mass and encrusting green microalgae (Chlorophyta, Charophyta) were also found. In Lake Turgoyak cortical green microalgae clearly dominated, together with other diatoms (Bacillariophyta: Rhopalodiaceae, Cocconeidaceae). Trichome and coccoid forms of cyanoprokaryotes (Cyanobacteria: Pseudanabaenaceae, Rivulariaceae, Chamaesiphonaceae, Microcystaceae) were also abundant. The colonisation of films by individual species varied among habitats and also depended on the surface microrelief.Conclusion. Analysis of the microplaston of LDPE films in hydrologically different habitats demonstrated the features of early colonisation of these substrates, the biotope‐specificity of the species and spatial structure of communities, as well as the organisation of colonial settlements of a number of species.